A Mathematical Formulation for Diamagnetism in Tetrahedrally Bonded Semiconductors - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
An expression for the magnetic susceptibility tensor corresponding to diamagnetic contribution in tetrahedrally bonded semiconductors is derived; this formulation refers to the crystalline state. In addition, a comparison with the amorphous case is outlined.